2023
DOI: 10.33271/mining17.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Deformation as a process to transform shape and volume of protective structures of the development mine workings during coal-rock mass off-loading

Daria Chepiga,
Iryna Bessarab,
Vitalii Hnatiuk
et al.

Abstract: Purpose is to assess deformation characteristics of protective structures while coal-rock mass off-loading to ensure wall rock stability as well as operating conditions of the development mine workings in coal mines. Methods. In a laboratory environment, uniaxial compression of protective structures has been applied on the models to identify the influence by deformation processes on the changes in their rigidness resulting from the shape and volume transformation. Findings. Under the deformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Literature review. The review of recent scientific works showed that the problem of the effective use of mineral depos its, in particular coal, is dealt with by technologists, ecologists and economists [1,2]. A coal mine as a natural resource con tains, in addition to coal, water, methane, and subsoil heat [3].…”
Section: Introductionmentioning
confidence: 99%
“…Literature review. The review of recent scientific works showed that the problem of the effective use of mineral depos its, in particular coal, is dealt with by technologists, ecologists and economists [1,2]. A coal mine as a natural resource con tains, in addition to coal, water, methane, and subsoil heat [3].…”
Section: Introductionmentioning
confidence: 99%